Pelatihan Penggunaan Aplikasi Whimsical untuk Meningkatkan Pemahaman Mahasiswa Terhadap Materi Perkuliahan - Ekaputra, Firdiawan (UNIB Press, 2024)
Skills in using technology are an important need for students in facing the challenges of a rapidly changing era. The purpose of this training activity is to increase student understanding of lecture material through the use of whimsical applications. Training activities for using the whimsical application to improve student understanding of lecture material were given to 22 first semester students of the Chemistry Education Study Program at Jambi University. The training was conducted on October 21, 2024 in room L-106 FKIP Jambi University. Training on the use of whimsical applications to improve student understanding of lecture material is carried out in five stages of activity, namely planning, preparation, implementation, and evaluation. Based on the training activities that have been carried out, the whimsical application has a positive influence on increasing students in using whimsical applications that can facilitate students in understanding lecture material, such as being able to present diagrams and mind maps that allow depicting the relationship between concepts more clearly. The use of the whimsical application allows students to work collaboratively, so as to speed up the process of discussion and completion of projects in groups.